(untitled) (Journal of Comparative & International Higher Education, 2022)
The COVID-19 pandemic has substantially impacted higher education. The unexpected move to online learning and support services have created many challenges. International students, who often are unfamiliar with the culture and norms of American higher education, have been particularly disadvantaged. Analyzing data received through an online survey, researchers identified the top five academic and non-academic challenges faced by international students during the pandemic, and their use of support services to overcome challenges. The results inform college administrators, professors, and student services professionals on the experiences of international students during the pandemic, and offer suggestions for reviving and expanding campus academic and social support services.